Dynamics of Bodybuild Indices in the Process of Complex Aerobic And Power Training Program - A. Aydarov, Rustam; ., . (International Journal of Engineering and Technology, 2018)
The aim of the article is to study the dynamics of the physique of girls involved in the program of complex physical training.The study involved 48 female university students who studied twice a week during 12 weeks. Running was chosen for aerobic exercise (6 hours), for power loads exercises with the overcoming of the weight of the body were used (12 hours). Anthropometric indices of the body were determined according to V.V. Bunak’s method using a standard set of instruments. We used analytical formulas were used by J. Matiegka to study the component composition of the body. The subjective evaluation of the impact of the training program was studied via a questionnaire.Results. The absolute fat content of the body decreased by 2.4 kg and the relative fat content –  by 4.7%.  We  revealed: 1) a decrease in the total thickness of skin-fat folds from 91.6 ± 5.0 mm to 74.2 ± 4.3 mm; 2) approximately the same rate of decrease in the thickness of skin-fat folds - 17.5 ± 0.16%, in different parts of the body; 3) the level of development of muscle mass has not changed, there is a tendency for its increase; 4) changes in the size of body girths did not occur, a tendency for their decrease  was noted; 5) the body mass index remained at the same level. Positive subjective assessments of a significant number of the girls engaged (81.3%) about the effect of the training program on the physique have been found.The training program of complex physical training allowed achieving a positive effect on the physique: to reduce the fat content, to maintain the level of development of muscle mass, body weight, body girths, gain muscle tone, positive affect on the emotional state and subjective assessments of changes in the state of physique.